Electrical properties of modified BNT based lead-free ceramics - Supalak Manotham (2018)
© 2016 Trans Tech Publications, Switzerland. The properties of modified Bi0.5Na0.5TiO3 (BNT) based lead-free ceramics were investigated. The BNT-based ceramics were prepared by a solid-state mixed oxide method Phase formation was determined by X-ray diffraction technique (XRD). The X-ray diffraction analysis of the ceramics suggested that all samples exhibited a perovskite structure without second phase. The value of dielectric constant increased with increasing in sintering temperature. Moreover, high sintering temperatures could improve ferroelectric properties of BNT base lead-free ceramics.